2012
DOI: 10.1158/1535-7163.mct-11-0503
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Vascular Endothelial Growth Factor Secretion by Childhood Acute Lymphoblastic Leukemia Cells via the FLT-3 Signaling Pathway

Abstract: Human leukemia cells secrete VEGF, which can act in a paracrine manner within the bone marrow microenvironment to promote leukemia cell survival and proliferation. The FLT-3 receptor tyrosine kinase plays an essential role in regulating normal hematopoiesis, but its constitutive activation via mutation in acute leukemias is generally associated with poor outcome. The aim of this study was to investigate interactions between the FLT-3 and VEGF signaling pathways in acute leukemia using cell lines and ex vivo cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…These findings support the notion that inhibition of Flt3 by AC220 affects retinal new vessel formation in the retina and detachment induced by VEGF in these models. Markovic et al showed that the Flt3-blocking antibody D43 decreased Flt3 tyrosine phosphorylation and reduced Flt3-induced VEGF secretion, indicating that Flt3 signaling is highly involved in VEGF regulation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the notion that inhibition of Flt3 by AC220 affects retinal new vessel formation in the retina and detachment induced by VEGF in these models. Markovic et al showed that the Flt3-blocking antibody D43 decreased Flt3 tyrosine phosphorylation and reduced Flt3-induced VEGF secretion, indicating that Flt3 signaling is highly involved in VEGF regulation [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may contribute to the observed suppression of angiogenesis in the livers of rats treated with folic acid and tributyrin. First, treatment of rats with folic acid and tributyrin alone or in combination caused down‐regulation of several key genes encoding activators of the angiogenesis signaling pathway, including Itgb6 , Itgad , Ftl3 , Map3k6 , Mgp and Src . It has been demonstrated that these proteins stimulate a VEGFA secretion through activation of the MAPK pathway (integrins, FLT3, MAP3K6 and SRC) or induction of the TGF‐β1 pathway (MGP).…”
Section: Discussionmentioning
confidence: 99%
“…First, treatment of rats with folic acid and tributyrin alone or in combination caused down-regulation of several key genes encoding activators of the angiogenesis signaling pathway, including Itgb6, Itgad, Ftl3, Map3k6, Mgp and Src. [32][33][34][35][36][37] It has been demonstrated that these proteins stimulate a VEGFA secretion through activation of the MAPK pathway (integrins, FLT3, MAP3K6 and SRC) or induction of the TGF-b1 pathway (MGP). Second, treatment of rats with folic acid and tributyrin alone, or a combination of folic acid and tributyrin resulted in marked down-regulation of the Edn1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Such varying microenvironmental milieus may impose considerably different survival stresses. Many hematologic malignancies elaborate significant amounts of VEGF with mounting evidence of a role in CNS breach [57, 58, 65, 7578]. Angiogenesis in this context may impose microenvironmental effects—increased microvessel density can correlate with worse prognosis/outcome in both lymphomatous mass/nodule and leukemic contexts [75, 77].…”
Section: Survival and Persistence Within The Cnsmentioning
confidence: 99%